PERAN TAMAN BACAAN MASYARAKAT (TBM) MANDHALA SENOM BAGI ANAK-ANAK DALAM MENINGKATKAN BUDAYA BACA - Qurrotul A’yun Sufyan, Qurrotul A’yun Sufyan; Dzat MR, Ahmad Faizal (CV. Jendela Gagasan, 2025)
Community Reading Park (TBM) is a non-formal education service that is present in the midst of the community to provide benefits and positive influences for the community. This non-profit oriented institution has a major influence in the empowerment process of the surrounding community. TBM Mandhala Senom is one of the TBMs that was established to provide free book reading services that can be utilized by the community, especially in the Pamekasan area for educational purposes. The purpose of this study is to determine the role of Community Reading Parks in fostering a culture of literacy in children. Introduction and efforts to instill literacy skills in children will affect character, increase knowledge and be a solution in life. This article is a qualitative descriptive study. The results of the study show that TBM as a facilitator of community reading will improve reading culture in children. Thus, it can act as a learning tool for both children and parents in expanding their knowledge.